Scaling issues and design of MEMS - Baglio, Salvatore (John Wiley & Sons, 2007)
Scaling Issues and Design of MEMS aims to improve the reader’s basic knowledge on modelling issues of complex micro devices, and to encourage new thinking about scaling effects. It will provide support for practising engineers working within the defence industry and will also be of welcome interest to graduate students and researchers with a background in electronic engineering, physics, chemistry, biology and materials science.